2006
DOI: 10.1371/journal.pbio.0040063
|View full text |Cite
|
Sign up to set email alerts
|

The Nicotinic Acetylcholine Receptor Dα7 Is Required for an Escape Behavior inDrosophila

Abstract: Acetylcholine is the major excitatory neurotransmitter in the central nervous system of insects. Mutant analysis of the Dα7 nicotinic acetylcholine receptor (nAChR) ofDrosophila shows that it is required for the giant fiber-mediated escape behavior. The Dα7 protein is enriched in the dendrites of the giant fiber, and electrophysiological analysis of the giant fiber circuit showed that sensory input to the giant fiber is disrupted, as is transmission at an identified cholinergic synapse between the peripherally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
146
1
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(157 citation statements)
references
References 55 publications
4
146
1
6
Order By: Relevance
“…In particular, the GF circuit pathway to the DLM contains a prominent cholinergic synapse connecting the peripherally synapsing interneuron (PSI) with the DLM motoneuron, which is often monitored for synaptic function ( Figure 3A) (Tanouye and Wyman 1980;Gorczyca and Hall 1984;Pavlidis and Tanouye 1995;Kuebler and Tanouye 2000;Kuebler et al 2001;Allen et al 2006;Fayyazuddin et al 2006). Defects in synaptic transmission are indicated as a failure to follow, with fidelity, moderate stimulation frequencies.…”
Section: Electrophysiological Deficits In Shi Ts1 Mutants Indicate Symentioning
confidence: 99%
“…In particular, the GF circuit pathway to the DLM contains a prominent cholinergic synapse connecting the peripherally synapsing interneuron (PSI) with the DLM motoneuron, which is often monitored for synaptic function ( Figure 3A) (Tanouye and Wyman 1980;Gorczyca and Hall 1984;Pavlidis and Tanouye 1995;Kuebler and Tanouye 2000;Kuebler et al 2001;Allen et al 2006;Fayyazuddin et al 2006). Defects in synaptic transmission are indicated as a failure to follow, with fidelity, moderate stimulation frequencies.…”
Section: Electrophysiological Deficits In Shi Ts1 Mutants Indicate Symentioning
confidence: 99%
“…Some animals have evolved fast motor circuits devoted to the generation of such behaviors, such as the giant fiber system in flies, the Mauthner cell in fish, or the lateral giant neurons of crayfish (Wyman et al, 1984;Edwards et al, 1999;Korn and Faber, 2005). Although much is known in these and in other systems about how escape behaviors are generated in response to abrupt stimuli such as mechanical disturbances, air puffs, or light flashes (Levi and Camhi, 2000;Fayyazuddin et al, 2006;Bhatt et al, 2007), we still know very little about how escape behaviors are generated in response to objects approaching on a collision course, as may be expected from potential predators (Yamamoto et al, 2003;Preuss et al, 2006;Santer et al, 2006;Oliva et al, 2007;Hammond and O'Shea, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Flies were tested for light-induced escape response in a custom-made apparatus according to Fayyazuddin et al (2006). Flies were individually aspirated into a 9 ϫ 2 cm Petri dish illuminated by four green light-emitting diodes (LEDs; peak wavelength, 572 nm) placed at 90°to each other.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we employed the giant fiber system (GFS), a well characterized circuit in Drosophila (Allen and Murphey, 2007), as a model to express different mutant forms of CaMKII using the Gal4-UAS system in apparently distinct components of the GFS. Considering that the circuit uses D␣7 nAChR for excitatory neurotransmission (Fayyazuddin et al, 2006), we found that driving constitutively active CaMKII postsynaptically during synapse formation and stabilization precipitated differential defects in synaptic transmission at different central cholinergic synapses, and this likely underlies observed effects in associated behaviors.…”
Section: Introductionmentioning
confidence: 92%